Macrospora leaf spot development conditions and resistance/tolerance of Brazilian commercially grown maize genotypes - Wordell Filho, João Américo; Ducatti, Rafael Dal Bosco; Nesi, Cristiano Nunes (Acta Scientiarum. Agronomy, 2023)
Macrospora leaf spot (MLS), caused by the fungus Stenocarpella macrospora, is one of the most important diseases affecting maize in Brazil. However, there are no MLS-resistant cultivars commercially available. Therefore, this study aimed to investigate the lesion expansion rate of MLS in four maize genotypes, leaf wetness duration (0-, 6-, 12-, 18-, 24-, 30-, 36-, 42-, and 54-hour post-inoculation), disease development severity in three maize genotypes, and resistance/tolerance levels to MLS in 141 maize genotypes commercially grown in Brazil. The estimates were performed using logistic models adjusted to the parameters analyzed, except for resistance/tolerance levels, which were analyzed using proposed severity and resistance scales. The experiment was carried out at the Laboratory of Plant Phytopathology of the Epagri/Cepaf, Santa Catarina State, Brazil, from 2016 to 2020. Disease resistance was significantly different among genotypes and fungal isolates. However, none of the genotypes showed resistance or high tolerance levels to MLS. Leaf wetness duration influenced maximum disease severity, and lesion expansion rate differed significantly among the genotypes tested. All information generated in this study is essential for breeding programs of maize for MLS resistance